2016
DOI: 10.1111/ppa.12586
|View full text |Cite
|
Sign up to set email alerts
|

Phylotype and sequevar variability of Ralstonia solanacearum in Brazil, an ancient centre of diversity of the pathogen

Abstract: The β‐proteobacterium Ralstonia solanacearum causes bacterial wilt of many plant species. Knowledge of phylotype and sequevar variability in populations of this microorganism is useful for implementing control measures, particularly host resistance. To this end, 301 isolates of R. solanacearum were collected from different geographic regions and hosts in Brazil. Their phylotype and sequevar characterization was used to determine the amount and distribution of phenetic and phylogenetic variability. Isolates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 34 publications
11
53
3
6
Order By: Relevance
“…Considering that these strains are probably endemic the high level of diversity encountered is expected and similar variability has been reported before in Brazil, especially for phylotype IIB by Santiago et al (2016) who reported four new sequevars for this phylotype some of which were found on potato. Here we report additional three new sequevars of phylotype IIB that are phylogenetically distinct from any of those described before.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Considering that these strains are probably endemic the high level of diversity encountered is expected and similar variability has been reported before in Brazil, especially for phylotype IIB by Santiago et al (2016) who reported four new sequevars for this phylotype some of which were found on potato. Here we report additional three new sequevars of phylotype IIB that are phylogenetically distinct from any of those described before.…”
Section: Discussionsupporting
confidence: 80%
“…which probably originated from the Brazilian Amazon basin and can have co-evolved with many plant species (Wicker et al, 2012; Santiago et al, 2016). This potato infecting taxon has spread world-wide and the reference sequences from all over the world are highly homologous suggesting clonal propagation and a relatively recent international dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is considered a putative centre of origin of Ralstonia solanacearum (phylotype II) (Wicker et al, 2012). However, R. pseudosolanacearum (phylotype I) has also been found associated with solanaceous crops, such as tomato, aubergine, long pepper and bell pepper (Santiago, Lopes, Caetano‐Anollés, & Mizubuti, 2017). Until now, only phylotype II has been reported causing BW in eucalypt in Brazil, but some reports indicate that phylotype I can also cause wilt symptoms in eucalypt in Africa and Asia (Carstensen, Venter, Wingfield, & Coutinho, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Durante seu ciclo esta planta sofre bastante devido a ocorrência de varias doenças, dentre elas as várias bacterioses, com destaque para a murcha bacteriana causada por R. pseudosolanacearum e R. solanacearum (SANTIAGO et al, 2016).…”
Section: Introductionunclassified